#TITLE_ALTERNATIVE# - Soenarto (NIM 322 94 011), Bambang
Abstract : Research in karst hydrology on the Joint Watershed of Surface and Subsurface River of Bribin - Baron, Gunung Kidul Regency, Yogjakarta Special Province, is intended to estimate its output discharge for determining water availability to be used in water resources management. The Joint Watershed consists of Surface (nonkarstic) Subwatershed and Subsurface (karstic) Subwatershed. The discharge of the Joint Watershed as a continuous function of time, has not been known yet. The availability of its data is very limited and in form of a scattered event, however, its output discharge is recognized to be perennial. The Joint Watershed is not in form of a well defined system, since a part of its boundary and area can not be determined due the complexity of karst conditions. The aquifer of the Surface Subwatershed is a limestone which has fractures and fissures, but with less intensity than in the Subsurface Subwatershed, and is not a granular rock. In the Subsurface Subwatershed surface river patterns are not recognized, instead, minor water routes are formed in the interhilly valley during rainy season. Water sinks immediately through fractures, fissures, caves and sinkholes, which are special characteristics of karstic areas. Thus, the data generation of historical daily discharge of the Joint Watershed is needed for determination of : (1) water avalability volume of the Joint Watershed and contribution of those two Subwatersheds, (2) area of the Joint Watershed (Subsurface Subwatershed), (3) delineation of the boundary of the Joint Watershed (Subsurface Subwatershed). Discharge data generation is carried out by applying models of a rainfall-runoff relationship and supported by results of research in other fields. Up to present the application of a nonkarstic watershed model to a karstic watershed is accomplished by the following approaches : (1) the area of the karstic watershed is determined explicitly based on estimation (delineation of the watershed boundary is determined in advance) or the area is not considered at all, (2) the use of observed long period continuous discharge data (time series). Two stochastic models of ARMA (Auto Regressive and Moving Average) using these approaches have been applied to Trebisnjica River, in a karstic area of Dinaric, Croatia. Such determination of the area means that the delineation of the boundary has been done subjectively in advance, whereas the complexity of the physical conditions results in difficulties in determining the area and boundary of a karstic watershed. In this research the use of models to estimate the discharge of a karstic watershed is carried out by the following different approaches : (1) the area of the karstic watershed is determined implicitly in the model during model calibration processes by assuming that the area is considered as one of the model parameters, (2) the observed discharge data is not necessarily continuous and in long periods since such requirements in karstic areas are rarely fulfilled. By considering the complexity of the physical conditions of nonkarstic and karstic areas and data availability of discontinuous disharge in a long time period, therefore, by observing the data patterns and using continuous daily rainfall and potential evapotranspiration data, the following hypothesis has been established as a basis for determining discharges of the Joint Watershed : High storage effect in the Joint Watershed, which is a function of the size of fractures and fissures, thickness and area of the media of fractures and fissures, results in the following output discharge characteristics : (1) recession curves with long periods and low recession curve coefficient, (2) low longterm monthly variation from one month to the following month (3) dominated by internal baseflow which mainly occurs in the Subsurface Subwatershed. Based on the storage phenomenon stated in the hypothesis, storage models have been chosen, with daily basis, and by assuming the area as one of model parameters. The storage models are Modified Sugawara Thornthwaite Model (MSTM), which is a joint model of Sugawara Tank Model and surplus calculation of hydrological balance model of Thornthwaite, and Combination of Autoregressive and Transfer Functions with Lag Time Model (CATFLTM). CATFLTM is specially applied to determine average lag time from rainfall events to discharge events. The application of MSTM is carried out based on the following way of thinking : (1) river flow hydrograph can be stated as a summation of exponential functions, (2) the outflows of side and bottom outlets of a tank model are in form of exponential functions, in which the number of outlet and parameter can be arranged in such a way that enable simulation of the discharge hydrographs of the Joint Watershed, (3) Sugawara tank model, as a separate component, is very flexible because of its ability to simulate linear as well as nonlinear systems. Water availability and the area of the Joint Watershed can be determined from MSTM when the following requirements are fulfilled : (1) multidisciplinary and interdisciplinary research performed on the considered area has enough information to start with, (2) incomplete data can be handled by using new and other supporting data obtained when the research goes on, (3) surplus and actual evapotranspiration are calculated from long term yearly hydrological balance since in this case the change of storage can be assumed to be zero. Modification for modeling purposes gives the following results : (1) a flowchart of karstic hydrological processes and its physical description (2) tank model analogy for the hydrological processes in the Subsurface Watershed, (3) tank arrangement for MSTM which consist of three variants of Lumped Model (LM) and four variants of Semi Distributed Model (SDM), (4) derivation of a modified flow scheme for the Joint Watershed. By using discontinuous observed discharge data of a time span of 1982 - 1998, the best simulation has been obtained from SDM of variant III with a pair of maximum soil moisture of 90 mm for the Surface Subwatershed and 40 mm for the Subsurface Subwatershed with representative rainfall of 1781 mm for the period of 1982 - 1998. The obtained average daily discharge for yearly long term for the Joint Watershed is 5,864 m3/s, for the Surface Subwatershed 1,778 m3/s and for the Subsurface Watershed 3,906 m3/s. The hypothesis has been verified by the following results : (1) the discharge recession curves has a long average recession period t of 213,7 days with low resultant coefficient of recession curve k of 0,0005 - 0,0030 for the karstic limestone, (2) the average variation of long term monthly discharges from one month to the next month is 6,13 %, (3) the long term yearly water availability of the Joint Watershed is 179,2 x 106 m3, 69% originates from the Subsurface Subwatershed, with the area of 178,92 km2, and 31% from the Surface Subwatershed, with the area of 117,67 km2. Other results obtained for the Joint Watersheds are : (1) the lag time of 275 days is obtained from CATFLTM, (2) the area is 296,59 km2, and consequently, the delineation of its imaginary boundary can be tentatively and hypothetically estimated on the map, (3) the obtained k range values show that the karstic limestone is very permeable, which is proposed to be added to the existing table of k values for various rocks. The results of the research in the Joint Watershed of Bribin - Baron are not much different from the Joint Watershed of Upstream Cetina, Bosnia Hercegovina, which has almost the same condition, and the character of the discharge of Sumber Baron is also almost the same as coastal springs of Dinaric karstic areas.